PDE1A inhibition elicits cGMP‐dependent relaxation of rat mesenteric arteries - Khammy, Makhala Michell (Br J Pharmacol, 2017)
BACKGROUND AND PURPOSE: PDE1, a subfamily of cyclic nucleotide PDEs consisting of three isoforms, PDE1A, PDE1B and PDE1C, has been implicated in the regulation of vascular tone. The PDE1 isoform(s) responsible for tone regulation is unknown. This study used isoform‐preferring PDE1 inhibitors, Lu AF58027, Lu AF64196, Lu AF66896 and Lu AF67897, to investigate the relative contribution of PDE1 isoforms to regulation of vascular tone. EXPERIMENTAL APPROACH: In rat mesenteric arteries, expression and localization of Pde1 isoforms were determined by quantitative PCR and in situ hybridization, and physiological impact of PDE1 inhibition was evaluated by isometric tension recordings. KEY RESULTS: In rat mesenteric arteries, Pde1a mRNA expression was higher than Pde1b and Pde1c. In situ hybridization revealed localization of Pde1a to vascular smooth muscle cells (VSMCs) and only minor appearance of Pde1b and Pde1c. The potency of the PDE1 inhibitors at eliciting relaxation showed excellent correlation with their potency at inhibiting PDE1A. Thus, Lu AF58027 was the most potent at inhibiting PDE1A and was also the most potent at eliciting relaxation in mesenteric arteries. Inhibition of NOS with l‐NAME, soluble GC with ODQ or PKG with Rp‐8‐Br‐PET‐cGMP all attenuated the inhibitory effect of PDE1 on relaxation, whereas PKA inhibition with H89 had no effect. CONCLUSIONS AND IMPLICATIONS: Pde1a is the dominant PDE1 isoform present in VSMCs, and relaxation mediated by PDE1A inhibition is predominantly driven by enhanced cGMP signalling. These results imply that isoform‐selective PDE1 inhibitors are powerful investigative tools allowing examination of physiological and pathological roles of PDE1 isoforms.